2005
DOI: 10.1086/502602
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acquisition of Clostridium difficile–Associated Diarrhea among Outpatients at a Cancer Hospital

Abstract: Background-Clostridium difficile-associated diarrhea (CDAD) is an important infection in hospital settings. Its impact on outpatient care has not been well defined. Objective-To examine risk factors of ambulatory cancer patients with CDAD.Design-Case-control study.Setting-Memorial Sloan Kettering Cancer Center, a tertiary-care hospital.Methods-Cases of CDAD among oncology outpatients from January 1999 through December 2000 were identified via positive C. difficile toxin assay results on stool specimen sent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 14 publications
3
45
1
3
Order By: Relevance
“…Risk factors for nosocomial CDAD in our veteran population are similar to risk factors found in other studies of veteran and nonveteran patients [13,16,[21][22][23][24][25][26][27]. Changela et al [25] studied veterans at the Hines VA (Chicago, IL) and found that levofloxacin use, the presence of comorbid conditions, and a higher mortality were associated with CDAD, but they did not examine spatial or seasonal trends, and the control group was not assayed for C. difficile, which may have allowed misclassification to occur.…”
Section: Discussionsupporting
confidence: 86%
“…Risk factors for nosocomial CDAD in our veteran population are similar to risk factors found in other studies of veteran and nonveteran patients [13,16,[21][22][23][24][25][26][27]. Changela et al [25] studied veterans at the Hines VA (Chicago, IL) and found that levofloxacin use, the presence of comorbid conditions, and a higher mortality were associated with CDAD, but they did not examine spatial or seasonal trends, and the control group was not assayed for C. difficile, which may have allowed misclassification to occur.…”
Section: Discussionsupporting
confidence: 86%
“…Hospitalization duration is a well-recognized risk factor for CDI. 21 This report has unique strengths. To our knowledge, this is the first integration of treatment-center-level practice data with cooperative group clinical trial data.…”
Section: Discussionmentioning
confidence: 94%
“…Increased length of hospital stay and number of hospital admissions continue to be identified as risk factors for CDI (7,50,70,114,134,146). This could be explained simply by the increased risk of exposure to C. difficile (transmission pressure) via, for example, the hands of health care workers or indirectly from the hospital environment.…”
Section: Difficile Transmission Pressurementioning
confidence: 99%